2022
DOI: 10.2147/clep.s380314
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Algorithms to Identify Acute Myocardial Infarction, Stroke, and Cardiovascular Death in German Health Insurance Data

Abstract: Validation of outcomes allows measurement of and correction for potential misclassification and targeted adjustment of algorithms for case definition. The purpose of our study was to validate algorithms for identifying cases of acute myocardial infarction (AMI), stroke, and cardiovascular (CV) death using patient profiles, ie, chronological tabular summaries of relevant available information on a patient, extracted from pseudonymized German claims data. Patients and Methods: Based on the German Pharmacoepidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A previous work conducted in data from the French National Healthcare Database (Système National des Données de Santé-SNDS) echoed by a German study demonstrated that anonymized patient profiles reconstituted from claims data (i.e., reconstituted electronic health records-rEHR) were a relevant material to conduct case adjudication. 3,4 The objective of this paper is to introduce the algorithm designed in the French SNDS to identify VTE in outpatient and inpatient settings, as well as the results of the intra-database validation conducted to assess its performance. This algorithm was developed, implemented, and validated in the framework of an international PASS study focused on the safety of baricitinib in patients with rheumatoid arthritis.…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…A previous work conducted in data from the French National Healthcare Database (Système National des Données de Santé-SNDS) echoed by a German study demonstrated that anonymized patient profiles reconstituted from claims data (i.e., reconstituted electronic health records-rEHR) were a relevant material to conduct case adjudication. 3,4 The objective of this paper is to introduce the algorithm designed in the French SNDS to identify VTE in outpatient and inpatient settings, as well as the results of the intra-database validation conducted to assess its performance. This algorithm was developed, implemented, and validated in the framework of an international PASS study focused on the safety of baricitinib in patients with rheumatoid arthritis.…”
Section: Purposementioning
confidence: 99%
“…Although the awareness of the risks related to outcome misclassification is high, 2 the implementation of classical validation studies relying on the linkage between claims records and patients' charts is not always possible for financial, technical, or legal issues. A previous work conducted in data from the French National Healthcare Database ( Système National des Données de Santé —SNDS) echoed by a German study demonstrated that anonymized patient profiles reconstituted from claims data (i.e., reconstituted electronic health records—rEHR) were a relevant material to conduct case adjudication 3,4 …”
Section: Purposementioning
confidence: 99%
“…Suppose one were interested in occurrence of serious acute nonfatal myocardial infarction (AMI). A primary algorithm might require a primary hospital discharge diagnosis of AMI 26,27 . To assess sensitivity of this algorithm in the study population, a more sensitive screening algorithm could be developed by relaxing the requirement that the AMI diagnosis be in the primary position thus including a discharge diagnosis of AMI in any position 28 .…”
Section: Validation To Inform Quantitative Bias Analysismentioning
confidence: 99%
“…Although the awareness of the risks related to outcome misclassification is high (2), the implementation of classical validation studies relying on the linkage between claims records and patients' charts is not always possible for financial, technical, or legal issues. A previous work conducted in data from the French National Healthcare Database (Système National des Données de Santé -SNDS) echoed by a German study demonstrated that anonymized patients profiles reconstituted from claims data (i.e., reconstituted electronic health records -rEHR) were a relevant material to conduct case adjudication (3,4).…”
Section: Purposementioning
confidence: 99%